Estimates of the Inflation Effect of a Global Carbon Price on Consumer, Investment, Export, and Import Prices - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper considers the potential inflation effects of a global carbon price on consumer prices, investment prices, export prices, and import prices. We estimate the effects under three different scenarios. The results clearly indicate that the inflation effects in developed countries of a 100 USD/ton carbon price are small. For developing countries, the inflation effect is larger and potentially too large for it to be politically feasible to introduce a global carbon price. However, a simple adjustment of the price based on the price level in each country equalizes the inflation effects across all countries, whereby a global carbon price is more likely to be implemented.
Keywords: E31; E52; Q54; Q58; 330; carbon price; inflation; consumer prices; export prices; imports prices; investment prices; monetary policy